Factors Influencing Pregnant Women'S Compliance In Attending Pregnancy Women'S Classes - Damanik, Muliani; Aini, Nur; Nasution, Ramadhani Syafitri (JKM (Jurnal Kebidanan Malahayati), 2025)
According to WHO data (2020), prenatal classes have been shown to reduce maternal mortality, as they provide information on pregnancy outcomes and prevent pregnancy-related complications. The WHO explains that approximately 287,000 women experience high-risk pregnancies. Data from the Sarulla Community Health Center (Puskesmas) indicates that 67.4% of those attending prenatal classes are far from the 100% target. The purpose of this study was to determine factors influencing pregnant women's adherence to prenatal classes in the Sarulla Community Health Center's work area in North Tapanuli Regency. The research design was analytical research using a cross-sectional approach. The population was all 67 pregnant women. The sample size was 67 pregnant women in their third trimester. Primary and secondary data were used. Data analysis used univariate, bivariate, and multivariate analysis using binary regression tests.The results of the study, obtained using a chi-square test, showed an effect of education on the participation of pregnant women in pregnancy classes, knowledge on the participation of pregnant women, distance to health facilities, the role of health workers, and family support. The most dominant factor was knowledge, which significantly influenced pregnant women's adherence to pregnancy classes in the Sarulla Community Health Center, North Tapanuli Regency. Conclusion: Education, knowledge, health workers, and family support influence the participation of pregnant women in pregnancy classes in the Sarulla Community Health Center. Health workers are expected to be more active in promoting the importance of pregnancy classes through various media such as integrated health posts (Posyandu), community health centers, social media, and other community activities. Keywords: Education, Knowledge, Distance to Facilities, Role of Health Workers, Family Support, Pregnancy Classes